2019
DOI: 10.1017/s1355617719000249
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cognitive Load Reveals Unilateral Neglect and Altitudinal Extinction in Chronic Stroke

Abstract: Objective: Neuropsychological studies suggest that the ability to compensate for the presence of spatial neglect highly depends on the attentional resources a patient can rely on. The present research aimed to study neglect in situations where attentional resources are limited due to multitasking. Method: We examined two patients more than 3 years after a right-hemispheric stroke. Both had received neuropsychological rehabilitation for left neglect and did not show any impairment in standard tests. We used a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 39 publications
(49 reference statements)
3
31
0
Order By: Relevance
“…However, most previous studies (e.g. Andres et al, 2019;Blini et al, 2016;Bonato, 2015;Bonato et al, 2010Bonato et al, , 2012, which have compared more complex computer-based tasks to pen-and-paper methods in the peripersonal space, have found that the computer-based tasks are more sensitive in identifying mild neglect. Which factors contributed to both large-screen tasks being sensitive in identifying RH patients' subclinical neglect?…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, most previous studies (e.g. Andres et al, 2019;Blini et al, 2016;Bonato, 2015;Bonato et al, 2010Bonato et al, , 2012, which have compared more complex computer-based tasks to pen-and-paper methods in the peripersonal space, have found that the computer-based tasks are more sensitive in identifying mild neglect. Which factors contributed to both large-screen tasks being sensitive in identifying RH patients' subclinical neglect?…”
Section: Discussionmentioning
confidence: 96%
“…Hence, a large test field may be one of the components that increase sensitivity. Further, a dual-task assignment presumably eliminates the typical top-down coping mechanism and brings out symptoms that would otherwise be compensated for (Andres et al, 2019;Bonato, 2015;Robertson & Frasca, 1992;Robertson & Manley, 2004;van Kessel et al, 2013). Increases in task demands need not be either visuospatial or attentional in order to improve assessment (Mennemeier, Morris, & Heilman, 2004;Ricci et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New tools for identifying neglect are continually being developed, possibly due to the existing tools not being able to detect milder forms of neglect, or an inability to detect the different neglect subtypes. The increasing number of virtual reality and computer-based tools being developed have the potential to increase the task demands, such as dual-task paradigms or speeded reaction time tests, in order to identify mild or subclinical neglect (121)(122)(123). However, many of these tools are not feasible to use in clinical settings due to the complex setup or cost requirements.…”
Section: Discussionmentioning
confidence: 99%